China's growth challenges - Wan-Hsin Liu; Rolf J. Langhammer (Kiel Institute for the World Economy (IfW), 2016)
Against the background of the continuously weaker economic growth in China in the past few years, the Chinese government is convinced that the Chinese economy needs to adapt itself to getting used to "the New Normal". Under "the New Normal" the Chinese economy will grow at lower rates of about 6-7% annually, whereas China would strive for substantial quality advancement that should become a core element in its future growth model in the long run. To realize a more quality- and domestic-market-oriented sustainable economic development, several reform measures need to be implemented and expanded and new reform policies need to be initiated. Focusing on three key growth challenges faced by China - domestic consumption, innovation and entrepreneurship, and foreign trade and investment, this paper aims at providing more insight into these challenges and sketching potential policy measures that are required to deal with them. Reforms and policy measures to be implemented need to have a clear long-term orientation to support adequate long-term structural changes, and such orientation requires consistency, credibility, and transparency in order to avoid confusing signals received by market participants. – – Vor dem Hintergrund einer in den vergangenen Jahren kontinuierlich zurückgegangenen Wachstumsrate der chinesischen Wirtschaft stellt sich für China die Herausforderung, die Wirtschaft an "die neue Normalität" (the New Normal) anzupassen. Unter "der neuen Normalität" wird die chinesische Wirtschaft nicht nur mit einer niedrigeren jährlichen Rate von etwa 6-7% weiter wachsen. Wichtig ist auch, dass die Qualität der wirtschaftlichen Entwicklung zunimmt. Dazu gehören vor allem Innovationen und ein effizienterer Ressourceneinsatz. Zu diesem Zweck müssen neue Reformschritte eingeleitet und die bereits verabschiedeten Reformmaßnahmen umgesetzt und erweitert werden. Das Papier gibt einen Einblick in die drei Kernherausforderungen, denen sich China stellen muss: die Förderung des einheimischen Konsums, die Unterstützung für Innovationen und privates Unternehmertum, sowie die weitere Öffnung Chinas im Außenhandel und gegenüber Auslandsinvestitionen. Damit Reformen Erfolge zeitigen, bedarf es der Konsistenz, Glaubwürdigkeit und Transparenz staatlicher Reformen und ihrer Vermittlung, um unklare bzw. verwirrende Signale an alle Marktteilnehmer zu vermeiden.
Keywords: 330